University of Pennsylvania General Alumni Society Membership Card - The General Alumni Society of the University of Pennsylvania:::::: (1954)
A membership card for the General Alumni Society of the University of Pennsylvania. Butner attended the university in 1911, studying under legendary Beaux-Arts architect and educator Paul Cret.